2005
DOI: 10.1107/s1600536805010731
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(2-Hydroxy-3,4-dimethoxyphenyl)-3-(4-hydroxyphenyl)prop-2-en-1-one

Abstract: The title compound, C17H16O5, crystallizes with two independent mol­ecules in the asymmetric unit. These are oriented approximately orthogonal to one another. The keto group adopts an s‐cis conformation; the six‐membered ring formed by the O—H⋯O hydrogen bond and the adjacent benzene ring are approximately coplanar. In addition to an intra­molecular O—H⋯O hydrogen bond, inter­molecular O—H⋯O inter­actions link adjacent mol­ecules into chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…The mean plane of the prop-2-en-1-one group, the active site in this molecule, makes angles of 3.6 (0)° and 2.6 (7)°, respectively, with the hydroxyphenyl and dimethoxyphenyl rings. Bond lengths and angles are normal (Allen et al, 1987) and corespond to those observed in related compounds (Butcher et al, 2006;Cao et al, 2005;Harrison et al, 2007;Jasinski et al, 2010Jasinski et al, , 2011aJasinski et al, , 2011bNgaini et al, 2009;Radha Krishna et al, 2005;Sharma et al, 1997;Wu et al, 2005). (Table 1) and π-π stacking interactions (Table 2, Fig.…”
Section: S1 Commentsupporting
confidence: 62%
See 1 more Smart Citation
“…The mean plane of the prop-2-en-1-one group, the active site in this molecule, makes angles of 3.6 (0)° and 2.6 (7)°, respectively, with the hydroxyphenyl and dimethoxyphenyl rings. Bond lengths and angles are normal (Allen et al, 1987) and corespond to those observed in related compounds (Butcher et al, 2006;Cao et al, 2005;Harrison et al, 2007;Jasinski et al, 2010Jasinski et al, , 2011aJasinski et al, , 2011bNgaini et al, 2009;Radha Krishna et al, 2005;Sharma et al, 1997;Wu et al, 2005). (Table 1) and π-π stacking interactions (Table 2, Fig.…”
Section: S1 Commentsupporting
confidence: 62%
“…For related structures, see: Butcher et al (2006); Cao et al (2005); Harrison et al (2007); Jasinski et al (2010Jasinski et al ( , 2011a; Ngaini et al (2009); Radha Krishna et al (2005); Sharma et al (1997); Wu et al (2005). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Chalcone rich plant extracts are used as drugs or food preservatives because of their radical quenching properties of the phenolic groups [16]. These outstanding properties of chalcones make them so important in theoretical and experimental studies [17][18][19]. Substitution on either of the benzene rings of chalcones greatly influences the non-centro-symmetric crystal packing.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the spacer formed by C10-C9-C8-C7-O1-C1 can be considered as a plane with a RMSD of 0.029 Å. This feature is also observed in other chalcones (Escobar et al 2008;Valdebenito et al, 2010;Chu et al 2004;Radha Krishna et al 2005;Wu et al 2005).…”
Section: Methodsmentioning
confidence: 86%
“…For bichalcone derivatives, see: Shetonde et al (2010). For related structures, see: Escobar et al (2008); Valdebenito et al (2010); Chu et al (2004); Radha Krishna et al (2005); Wu et al (2005). Data collection: CrysAlis PRO (Agilent, 2011); cell refinement: CrysAlis PRO; data reduction: CrysAlis PRO; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: OLEX2 (Dolomanov et al, 2009); software used to prepare material for publication: OLEX2.…”
Section: Related Literaturementioning
confidence: 99%